АДАПТАЦИЯ СТУДЕНТОК К ОБУЧЕНИЮ В ВУЗЕ, МОРФОЛОГИЧЕСКИЕ И ФУНКЦИОНАЛЬНЫЕ ОСОБЕННОСТИ (Experimental biology, 2015)
Process of adaptation to training in high school is accompanied by change of morphological and functional indicators of cardiovascular, respiratory systems, factor of health and is connected with duration and residing conditions in the given region and increase in intellectual loading.
Keywords: adaptation